2022
DOI: 10.3389/fpls.2022.835414
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Physiological Changes in the Roots of Two Oat Cultivars in Response to Complex Saline-Alkali Stress

Abstract: Saline-alkali stress is a major abiotic stress factor in agricultural productivity. Oat (Avena sativa L.) is a saline-alkali tolerant crop species. However, molecular mechanisms of saline-alkali tolerance in oats remain unclear. To understand the physiological and molecular mechanisms underlying seedling saline-alkali tolerance in oats, the phenotypic and metabolic responses of two oat cultivars, Baiyan7 (BY, tolerant cultivar) and Yizhangyan4 (YZY, sensitive cultivar), were characterized under saline-alkali s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…However, the relative content of the above metabolites in the alkaline stress group was less than that in the control group, indicating that root cells are still affected by alkaline stress damage and affect growth. Results similar to previous report where phenylalanine accumulation was downregulated in oat roots by saline‐alkali stress, suggesting that phenylpropanoid biosynthesis was partially inhibited (Gao et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…However, the relative content of the above metabolites in the alkaline stress group was less than that in the control group, indicating that root cells are still affected by alkaline stress damage and affect growth. Results similar to previous report where phenylalanine accumulation was downregulated in oat roots by saline‐alkali stress, suggesting that phenylpropanoid biosynthesis was partially inhibited (Gao et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Soil salinity and alkalinity are the most important abiotic stress factors affecting plant health and growth. The roots are the primary organs responsible for nutrient and water absorption from the soil and are more sensitive to salt and alkali stress compared to other plant tissues (Gao et al, 2022). Saline‐alkali stress may adversely affect the establishment of the symbiotic relationship between AMF and plants and lead to a decrease in the number of endospores, mycelium, vesicles, and arbuscles in plant roots (Qin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Because metabolites are the end products of biological systems, changes in metabolic levels in organisms are expected to be connected with phenotypes. Numerous Plants 2023, 12,1916 2 of 15 studies have confirmed that some metabolites, such as proline, betaine, organic acids, soluble sugars, nitrogen compounds, and polyols, are beneficial in improving plant salt tolerance [3,6,7]. Meanwhile, plants also need to accumulate specific metabolites to balance intracellular pH in addition to the metabolites listed above under alkali stress.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, plants also need to accumulate specific metabolites to balance intracellular pH in addition to the metabolites listed above under alkali stress. Among these, organic acid accumulation is a form of plant adaptation to high pH; multiple studies have demonstrated that an increase in organic acid concentration improved plants' alkali stress resistance [6,7]. Metabolite accumulation involves the activation of metabolic processes, and plants enhance metabolite accumulation by activating metabolic pathways, hence strengthening stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation